Heavy Metals and PAHs in Meat, Milk, and Seafood From Augusta Area (Southern Italy): Contamination Levels, Dietary Intake, and Human Exposure Assessment - Di Bella, Calogero; Traina, Anna; Giosuè, Cristina; Carpintieri, Davide; Lo Dico, Gianluigi Maria; Bellante, Antonio; Del Core, Marianna; Falco, Francesca; Gherardi, Serena; Uccello, Maria Michela; Ferrantelli, Vincenzo (Frontiers in Public Health, 2020)
Heavy metals and PAHs were measured in animal foodstuffs from Augusta-Melilli-Priolo area in order to evaluate the potential human health risk associated to their consumption. All heavy metals were detected in seafood products while most of them were <LOD in beef, pork and milks samples. Particularly, seafood products registered higher values of total arsenic (As), mercury (Hg) and lead (Pb) than other food categories, while beef and pork showed higher content of zinc (Zn). Cadmium (Cd) and Pb were below the tolerable limits reported by the European Union in foodstuffs (1) while mercury exceed the threshold value in seafood products. Among the PAHs, chrysene (Chr) was detected in all the terrestrial foodstuffs with higher concentrations found in raw milks. Small quantity of benz(a)anthracene (BaA) were also found in this food. The health risk for consumers was assessed for five age categories of consumers calculating the estimated weekly intake (EWI), the target hazard quotient (THQ) and the cancer risk (CR) for each contaminant. Moreover, the margin of exposure (MOE) was estimated for PAHs. The EWIHg related to seafood products intake exceeded the Provisional Tolerable Weekly Intake (PTWI) recommended by the European Food Safety Authority. The THQHg was >1 for baby, children and teenagers, indicating a non-carcinogenic risk for these age categories by seafood ingestion. The CRAs overcame 1*10−5 for almost age categories (except “baby”) and for elderly, by seafood and beef ingestions respectively. Moreover, the MOE for PAHs showed a certain cancer risk for “baby” related to cow milk ingestion.